ANALISIS NILAI DAN PENGETAHUAN IBU-IBU RUMAH TANGGA SEBAGAI PREDIKTOR INTENSI BELI PRODUK SAYURAN ORGANIK DI PASAR MODERN KOTA PEKANBARU - Elfi Rahmadani dan Penti Suryani (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
This study was conducted at three sites of the modern market, in District Tampan and Payung Sekaki. The purpose of the study was to determine the characteristics and socio-economic conditions of the mother-housewife who buy organic vegetable products in the modern market Pekanbaru, and seek and reduce exploratory factor that can explain the influence of purchasing intentions housewife to organic vegetables. This study tested simultaneously and partially of predictor variables were examined to the intention to buy organic vegetable products in accordance with the design of the model. Descriptive quantitative research method is using factor analysis and path analysis. The study was conducted by a survey and interviews with respondents using questionnaires. Sampling was done by the method of accidental sampling a number of 103 respondents each of 3 modern market. The results showed all hypothesis is accepted. The main factors that influence the cost of the purchase of vegetables, the age of the buyer, the number of family members buyers, and home ownership, then the second factor of the level of education and the third factor the amount of consumption of vegetables. Knowledge of organic crops have a positive and significant impact on the attitude of the organic vegetables. Variable value of the natural orientation and attitude to the intention to buy organic vegetables have validity and reliability of the positive value. Organic Knowledge also has a positive and significant impact on the attitude of organic vegetables. Attitudes on organic vegetables also have a positive and significant impact on the purchasing intentions of organic vegetables